Protective Factors Associated With Fewer Generalized Anxiety Disorder Symptoms Among Women Exposed to Intimate Partner Violence - Schaefer, Lauren M. (Journal of interpersonal violence, 2021)
Generalized anxiety disorder (GAD) has received minimal empirical attention in the context of intimate partner violence (IPV). Furthermore, factors related to lower levels of GAD symptoms in this population have received limited focus. This study evaluated the protective role of four forms of support, spiritual, family, friend, and community, in predicting levels of generalized anxiety among women who have experienced recent IPV. Participants included 116 women who were recruited from local agencies serving IPV-exposed individuals. Participants completed measures of IPV, GAD, stressful life events, spiritual support, social support, and community support during a 1-hr interview. Findings from a hierarchical multiple regression analysis indicated that after accounting for age, income, mental health service utilization, stressful life events, and severity of IPV, lower GAD symptoms were only associated with higher spiritual support (β = −0.20, p = .02) and community support (β = −0.25, p = .01), not friend or family support, F(9, 114) = 5.10; p < .001; R2 = .30. These findings indicate that alternative sources of support (i.e., spiritual and community) may be more accessible for IPV-exposed women, contributing to their association with reduced GAD symptomatology. The current study highlights the potential for spiritual and community support to serve a beneficial role above and beyond standard social support proffered by friends and family on symptoms of GAD. Results reinforce the examination of a broad range of multiple supports among women experiencing IPV. This thorough examination of different support systems may provide further insight into novel resources that can be strengthened among IPV-exposed populations.